G548(P) Special requirements in blood transfusion – an audit of requesting errors. (27th April 2015) - Morgan, I; Harrison, E; Nicholson, F
Abstract : Context: This Audit was conducted in a tertiary haematology/oncology unit to identify errors in red cell transfusion requests by unit nursing and medical staff. Problem: When requesting blood it is important to consider whether the patient has any special transfusion requirements, most common being the need for CMV screened or irradiated blood products. It is important to request these for patients who require them and significant harm can be caused to patients if they don't receive what they need (Figure 1 ). It is equally key to avoid wasting these resources; Irradiation reduces shelf life of blood, and over-requesting CMV negative blood reduces availability for those who need it. Incorrect use is currently picked up by blood bank staff, there is no safety net in place. Assessment of problem and analysis of its causes: The list of red cells used for transfusion kept by bloodbank was audited, looking at who requested the transfusion and what special requirements they requested. This was compared against what each patient should have had requested, and discrepancies were identified. Initially 2 months of blood requests were audited and showed 3/37 and 7/57 errors. There has therefore been discussion amongst haematology and blood bank across the city regarding measures to reduce this and re-audit conducted. Intervention: Three measures have been introduced: Alerts on the computer system for patients with special transfusion requirements A citywide guideline of which scenarios or patients warrant these requirements A form held by blood bank for each patient detailing their requirements, created at their first transfusion Study design: This was an audit and had a prospective design Strategy for change: The results were discussed in conjunction with other local haematology departments. The staff of the haematology/oncology unit were given access to the agreed guideline of which types of patients have special transfusion needs, trakcare alerts were implemented and blood bank agreed on forms that they would hold. These were in place for a year prior to reaudit. Following the results of re-audit, a presentation at a departmental meeting highlighted ongoing issues. Measurement of improvement: Following the interventions the results were analysed simply to show percentage change pre- and post intervention. The results showed a large increase in the number of incorrectly requested transfusions from an average of 10% error per month to 38% per month. The majority of errors were due to over-requesting special requirements (30%), but there was also a significant amount of missed requirements (8%). The majority of errors were related to CMV requesting (69%). The alerts on the computer system relating to special requirements were also looked at. 25% of patients had alerts. 6 of these had alerts when, according to the guideline, they are not required and 4 who do have special requirements did not have an alert. Effects of changes: There are still a high number of errors and this clearly is an ongoing problem with an impact on patient safety. On discussion several issues have been highlighted. Trakcare alerts have not been publicised to staff and there is limited knowledge of the intranet guideline, which is particularly relevant at night when the unit is covered by an on call team. Blood bank find the individual patient forms cumbersome and find it difficult to track down medical staff to fill them in. Lessons learnt: This audit has shown that there are ongoing errors in this area. The interventions in place have not fully addressed this and further work is needed. Message for others: This audit has identified a key patient safety issue. The misrequesting of blood can cause significant harm and the interventions tried so far have proved cumbersome. Further work is ongoing in this area.